Think Pair Share Method to Improve Learning Outcomes at Class VII MTsS PP Syafa'aturrasul Taluk Kuantan - Lilis Lendrayanis (Universitas Lancang Kuning, 2019)
This study aims to determine the learning outcomes of English students of class VII MTsS PP Syafa’aturrasul Taluk Kuantan Academic Year 2014/2015 through the application of Think Pair Share method. This research is classroom action research (CAR), by analyzing descriptively. This study consisted of two cycles. Retrieval of data in this study was conducted from September to October 2014. Subjects in this study were students of class VII, which amounted to 36 students consisting of 20 men and 16 women. Based on the analysis of data obtained by researchers, the absorption of students before CAR is 73.1. After CAR in cycle I is 80.8. In the second cycle of 85.3. Based on the results of the study indicate that the application of the Think Pair Share method can improve the learning outcomes of English in VII class students of MTsS PP Syafa’aturrasul Taluk Kuantan Academic Year 2014/2015.